Ligusticopsis miyiensis (Apioideae, Apiaceae), a new combination from China revealed by morphological and molecular evidence - Lei, Jia-Qing; Cai, Jing; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2023)
Ligusticum glaucescens (Apioideae, Apiaceae) found in China, is a poorly known species known only from the type collection. The species was considered to belong to Kitagawia. In our morphological examination, Ligusticum glaucescens is more morphologically consistent with Ligusticopsis than Kitagawia. Furthermore, several morphological characteristics of Ligusticum glaucescens can also easily distinguish this species from other validated Ligusticopsis species. Phylogenetic analyses based on plastome and nrDNA sequences revealed that Ligusticum glaucescens is distant from Kitagawia but nested in Ligusticopsis. As both morphological and phylogenetic evidence supported the inclusion of Ligusticum glaucescens within Ligusticopsis, this species is here transferred, and a new combination, Ligusticopsis miyiensis, is proposed.